“Input/output cytokines” in epidermal keratinocytes and the involvement in inflammatory skin diseases - Morizane, Shin; Mukai, Tomoyuki; Sunagawa, Ko; Tachibana, Kota; Kawakami, Yoshio; Ouchida, Mamoru (Frontiers in Immunology, 2023)
Considering the role of epidermal keratinocytes, they occupy more than 90% of the epidermis, form a physical barrier, and also function as innate immune barrier. For example, epidermal keratinocytes are capable of recognizing various cytokines and pathogen-associated molecular pattern, and producing a wide variety of inflammatory cytokines, chemokines, and antimicrobial peptides. Previous basic studies have shown that the immune response of epidermal keratinocytes has a significant impact on inflammatory skin diseases. The purpose of this review is to provide foundation of knowledge on the cytokines which are recognized or produced by epidermal keratinocytes. Since a number of biologics for skin diseases have appeared, it is necessary to fully understand the relationship between epidermal keratinocytes and the cytokines. In this review, the cytokines recognized by epidermal keratinocytes are specifically introduced as "input cytokines", and the produced cytokines as "output cytokines". Furthermore, we also refer to the existence of biologics against those input and output cytokines, and the target skin diseases. These use results demonstrate how important targeted cytokines are in real skin diseases, and enhance our understanding of the cytokines.